Analysis of Serving Leadership and Training Impacts Employee Engagement and Employee Performance Study Case Freight Forwarder Companies - Susanto, Primadi Candra; Sawitri, Ni Nyoman; Ali, Hapzi; Tussoleha Rony, Zahara (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study is expected to make a significant contribution to the development of freight forwarder companies in Jakarta as well as human resource management literature. This study uses a quantitative approach to examine the relationship between the variables studied, namely service leadership, training, employee performance, and employee engagement in freight forwarder companies in Jakarta. The population in this study is all freight forwarder companies operating in DKI Jakarta, which number 337 companies. From this population, 6 freight forwarder companies were selected that were considered representative and able to represent the characteristics of the population as a whole. Sample selection is carried out by purposive sampling, namely selecting companies that meet certain criteria such as company size, operational volume, and geographical location. Of the 6 companies, a sample of 105 respondents consisting of EMKL (Sea Cargo Expedition) operational staff was taken. The selection of respondents was carried out by stratified Random sampling to ensure that each sub-group in the population was proportionally represented. Servant Leadership has a significant positive influence on the Employee Performance variable, Training has a positive but not significant influence on the employee performance variable, Servant Leadership shows a significant positive influence on the Employee Engagement variable, Training also has a significant and positive influence on Employee Engagement, as well as Employee Engagement has a significant positive influence on Employee Engagement Employee Performance variable. No Effect of Servant Leadership through Employee Engagement on Employee Performance, and No Effect of Training through Employee Engagement on Employee Performance.